Performance Government: A Roundtable Discussion - Staff, Editorial (Maine Policy Review, 1999)
Many states have undertaken initiatives similar to the National Performance Review; the general term used to describe these activities is “performance government.” Although performance government may apply to a wide range of administrative changes, it most typically applies to three reform initiatives: strategic planning, performance budgeting and performance contracting. Maine has been reinventing its government systems to include each of these components. This roundtable discussion, co-facilitated and co-edited by Bruce Clary and Barton Wechsler, features eight individuals who have been helping to shape the reinvention of Maine state government: besides Clary and Wechsler, these include: Carolyn Ball, Charles Colgan, Merton G. Henry, Elizabeth Mitchell, Don Nicoll and Janice Waldron. Through their unique vantage points, they illustrate the complex set of factors—political, organizational, and technical—that have an impact on government reform and the prospect for meaningful change.